JURNAL PERANCANGAN SISTEM INFORMASI PERGUDANGAN SEDERHANA PADA CV JASMINE MOTOR BERBASIS WEB - Ayu Anita Jasmine (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The inventory stock system that is managed manually by CV Jasmine Motor has very limitations, CV Jasmine Motor realizes that manual data collection is very inefficient because it requires a lot of energy and time. Therefore, the authors develop a system that is able to assist the process of recording the existing inventory. To assist in this proccess the author makes a web-based application that aims to overcome problems in recording inventory manually and minimize errors in recording manually. With this application, it is able to provide convenience for warehouse staff to manage inventory stock through the application without having to search for the item in the warehouse, making it easier and more practical.